Evidence, Experiment and Argument in Linguistics and the Philosophy of Language - Hinton, Martin; Hinton, Martin (Peter Lang, 2016)
This volume is concerned with issues in experimental philosophy and experimental linguistics. Examining experiments in language from a variety of perspectives, it asks what form they should take and what should count as evidence. There is particular focus on the status of linguistic intuitions and the use of language corpora. A number of papers address issues of methodology in experimental work, while other contributions examine the use of thought experiments and what the hypothetical can tell us about the actual. The aim of this collection is to bring together the work of linguists and philosophers in order that they may learn from one another, and to help both groups understand how the use of experimental methods can affect the arguments they employ and the claims they make.